Design of polycationic micelles by self‐assembly of polyethyleneimine functionalized oligo[(ε‐caprolactone)‐co‐glycolide] ABA block copolymers†. (29th September 2016) - Balk, Maria; Behl, Marc; Yang, Jing; Li, Qian; Wischke, Christian; Feng, Yakai; Lendlein, Andreas
Abstract : Cationic polymeric micelles are of interest as delivery materials for nucleotides allowing condensation and transport of anionic macromolecules and enabling the reduction of cytotoxicity of polyethyleneimine, the current standard of vectors for non‐viral nucleic acid delivery. In addition, micelles based on a degradable core would be capable to degrade hydrolytically and release their payload, which should preferably occur after uptake in early endosomes providing a pH of 5.5. We explored whether degradable and amphiphilic ABA block copolymers from hyperbranched polyethyleneimine A blocks and B blocks based on hydrophobic oligoesters (CG) can be created, which can degrade in a pH range relevant for the early endosomes. CG was synthesized by ring‐opening polymerization of ε ‐caprolactone and diglycolide. Polycationic micelles with particle sizes between 19 ± 1 and 43 ± 2 nm were obtained by self‐assembly of the ABA block copolymers with different chain lengths of B blocks and/or co‐assembly with a diblock copolymer from poly(ethylene glycol) (PEG) functionalized CG oligoester in phosphate‐buffered saline solution. Mixed micelles containing PEG‐CG showed a decreased zeta potential, suggesting a shielding by dangling PEG chains at the micelle surfaces. Sizes of cationic micelles were stable at pH = 7.4 over the studied time period of 2 weeks at 37 °C. The hydrolytic degradation was controlled by the composition of the CG core and was accelerated when the pH was decreased to 5.5 as detected by increasing micelle sizes. In this way, the polycationic micelles may act as an on‐demand delivery system of condensed macromolecules. Copyright © 2016 John Wiley & Sons, Ltd.